The APISS Questionnaire: A New Tool to Assess the Epidemiology of Systemic Allergic Reactions to Bee Venom in Beekeepers - Carli Tanja; Košnik Mitja; Zaletel Kragelj Lijana; Burazeri Genc; Kukec Andreja (Sciendo, 2023)
To develop and validate a comprehensive questionnaire to be used as an instrument in cross-sectional studies among beekeepers.